Study on the fracture behavior and critical slowing down characteristics of saturated sandstone based on acoustic emission and resistivity - Yantao Zheng; Changwu Liu; Kunpeng Lu; Hexing Zhang; Bingxi Jian; Wuzhou Zhang (Scientific Reports)
Abstract Water significantly affects the fracture behavior and acoustic emission (AE) characteristics of sandstone, which is crucial for assessing the stability of underground engineering. This study investigates the fracture behavior of four types of saturated sandstone (green, white, brown, and red) using AE and resistivity monitoring techniques during uniaxial compression tests. AE energy, resistivity, and RA–AF parameters were analyzed to comprehensively assess the fracture behavior. Additionally, precursor information of sandstone failure was examined using the critical slowing down theory. The results revealed a decrease in uniaxial compressive strength and elastic modulus in saturated sandstone, with water softening effects ranked as brown, red, white, and green sandstone. Resistivity variation was highly sensitive to fracture development and demonstrated strong complementarity with AE signals. Crack classification based on the RA–AF parameter aligned with macroscopic failure patterns. Water presence accelerated the initiation of tensile cracks, with growth rates of 13.66%, 13.69%, 14.86%, and 17.53%, correlating with porosity and pore water pressure. The sharp increase in the autocorrelation coefficient and variance of AE parameters (amplitude, RA value, rise time, AE energy) before critical failure indicated a critical slowing down phenomenon, serving as a potential precursor to sandstone failure. Moreover, the sensitivity and reliability of critical slowing down theory in early warning applications were affected by water and porosity, which should be considered in practice.